Winning in a "lose-lose" environment of economic development: housing, community empowerment, and neighborhood redevelopment in the Columbia Heights neighborhood of Washington, DC. Issue 1 (2nd January 2020) - Howell, Kathryn L.
ABSTRACT: Economic development is often billed as the basis and justification for neighborhood revitalization in low-income communities, bringing with it new jobs, amenities, and residents. Best practices in local housing policy suggest that inclusionary zoning can be a remedy to the increasingÂ home prices and rents resulting from the changing demographics. However, inclusionary zoning remedies have been largely insufficient and remain part of a negotiated package of community benefits that do not reflect that collective agency of the existing community. This paper examines how tenant-centered affordable housing and community-based planning can provide a useful counter-narrative to the economic development and community benefits stories of the back-to-the city era urban redevelopment in Washington, DC. While DC has developed progressive laws and resources to enable low-income residents to remain in their communities, the fast-moving market has exposed conflicts between social and economic goals. Using the example of neighborhood revitalization efforts in Washington, DC, I examine the often-conflicting how economic development goals interact with community empowerment and the mechanisms to enable community control that change how residents experience revitalization.